Phytosanitary management of ICARDA’s Genebank seed collections for safe movement - Kumari, Safaa (International Center for Agricultural Research in the Dry Areas, 2024)
In celebration of the 100th anniversary of the establishment of the Research Institute of Plant Genetic Resources, the International Scientific Symposium on the theme “The Role of Plant Genetic Resources in Ensuring Food Security in the Face of Climate Change”, was held in Tashkent, Uzbekistan from 7 to 9 November 2024. Around 200 participants from over 20 countries were attended the symposium. The main objective of this symposium was to discuss current issues related to the conservation and use of plant genetic resources, develop international cooperation, and identify new areas for scientific research. During the symposium, a number of issues were discussed, such as: Conservation and use of plant genetic resources in conditions of global climate change; The role of plant genetic resources in ensuring food security; Modern biotechnological methods for the study and use of plant genetic resources; Innovative approaches of developed and developing countries in solving agricultural problems; Rational use of biological and non-biological resources in conditions of water scarcity; Exchange and cooperation in the field of plant genetic resources at the international. Dr Safaa Kumari (Head of ICARDA Seed Health Lab/Plant Virologist), presented “Phytosanitary Management of ICARDA’s Genebank Seed Collections for Safe Movement"